Characteristics and potential biomarkers of adult sickle cell patients with chronic pain. (1st July 2020) - Albo, Camila; Kumar, Sanjiv; Pope, Michael; Kidwell, Kyle Michael; Xu, Hongyan; Bowman, Latanya; Wells, Leigh; Barrett, Nadine; Fields, Sabine; Bora, Pritam; Patel, Niren; Kutlar, Abdullah
Abstract: Objectives: In this study, we investigated the evolution of chronic pain in sickle cell patients (SCD) as an age‐dependent phenomenon and studied the frequency of vaso‐occlusive episode frequency, opioid use, quantitative sensory testing (QST), and biomarkers of chronic pain (CP). Methods: We undertook a cross‐sectional study of the evolution of CP in SCD. A total of 72 subjects (age 15‐66) were enrolled. VOE frequency, presence of CP hydroxyurea (HU) therapy, opioid use, and laboratory parameters were collected. QST was performed, and plasma tryptase, substance P, and NGF (Nerve Growth Factor) levels were assayed. Results: There was an age‐dependent increase in frequency of CP, VOEs, opioid use, and Von Frey monofilament values. CP patients had significantly higher opioid use (daily morphine equivalents) (52.8 mg vs 6.94 mg, P = .009), suggesting a correlation between opioid use and hyperalgesia. NGF levels were also significantly higher ( P = .051). Our results confirm previous observations of an age‐dependent increase in the proportion of patients with CP and support the contributing role of mast cell activation and neurogenic inflammation. Conclusions: This is the first study of NGF as a possible biomarker of CP in SCD. If confirmed, this could provide a diagnostic marker and therapeutic target for CP in SCD.